Perturbation in the E1Π (v=0) state of the AlH molecule. - Szajna, Wojciech; Hakalla, Rafał; Zachwieja, Mirosław; Piotrowska, Izabela; Ostrowska-Kopeć, Małgorzata; Kolek, Przemysław; Kępa, Ryszard (The 23nd Colloquium on High Resolution Molecular Spectroscopy, Budapest, Hungary, 2013)
Perturbation in the E1Π (v=0) state of the AlH molecule.
Keywords: Perturbation in the E1Π (v=0) state of the AlH molecule.